1990
DOI: 10.1182/blood.v76.10.1997.bloodjournal76101997
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19-induced perturbation of human megakaryocytopoiesis in vitro

Abstract: Parvovirus B19 infection leads to transient aplastic crises in individuals with chronic hemolytic anemias or immunodeficiency states. An additional unexplained sequela of B19 infection is thrombocytopenia. Because B19 is known to have a remarkable tropism for human erythropoietic elements, and is not known to replicate in nonerythroid cells, the etiology of this thrombocytopenia is uncertain. We sought to define the pathobiology of B19-associated thrombocytopenia by examining the role of B19 on in vitro megaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 0 publications
1
39
1
2
Order By: Relevance
“…The NS1 gene of B19V may be responsible for this direct cytotoxicity to megakaryocytes. 12 An inhibitory effect of this NS1 protein on the colony-forming ability of megakaryocytic progenitor cells in vivo was confirmed in an animal model of parvovirus infection. The degree of inhibitory effect was dependent on the parvovirus infective load, and the depletion of megakaryocyte progenitor cells in the bone marrow appeared to coincide with erythroid progenitor depletion.…”
Section: Introductionmentioning
confidence: 85%
“…The NS1 gene of B19V may be responsible for this direct cytotoxicity to megakaryocytes. 12 An inhibitory effect of this NS1 protein on the colony-forming ability of megakaryocytic progenitor cells in vivo was confirmed in an animal model of parvovirus infection. The degree of inhibitory effect was dependent on the parvovirus infective load, and the depletion of megakaryocyte progenitor cells in the bone marrow appeared to coincide with erythroid progenitor depletion.…”
Section: Introductionmentioning
confidence: 85%
“…of B19 beyond the erythroid progenitor cell [Murray et al, 1994]. Previous studies also demonstrated that NS-1 protein, produced by parvovirus B19, could inhibit megakaryocyte colony formation [Ozawa et al, 1988;Srivastava et al, 1990]. Whether B19 infection is implicated in the pathogenesis of ITP in adult patients remains controversial [Lefrere et al, 1989;Van Elsacker-Niele et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Parvoviruses have a remarkable tissue tropism for erythroid elements in the bone marrow and are known to cause transient aplastic crisis in patients with various haemolytic anaemias (Young & Brown, 2004) but their relationship to platelets is not well documented. In vitro exposure of human bone marrow cells to parvovirus has been shown to significantly suppress megakaryocyte colony formation (Srivastava et al, 1990). This may be the mechanism of amegakaryocytic thrombocytopenic purpura secondary to parvovirus.…”
mentioning
confidence: 99%